Congenital Chagas disease involves Trypanosoma cruzi sub-lineage IId in the northwestern province of Salta, Argentina - Corrales, Rosa M. (2009)
Trypanosoma cruzi is genetically classified into six discrete phylogenetic lineages on the basis of different genetic markers. Identifying lineages circulating among humans in different areas is essential to understand the molecular epidemiology of Chagas disease. In the present study, 18 T. cruzi isolates from congenitally infected newborns in the northwestern province of Salta-Argentina were studied by multilocus enzyme electrophoresis (MLEE) and random amplified polymorphic DNA (RAPD). All isolates were typed by MLEE and RAPD as belonging to T. cruzi IId. Analysis of minor variants of TcIId using probes hybridizing with hypervariable domains of kDNA minicircles, detected three variants with a similar distribution among the isolates. Our findings confirm the presence of T. cruzi IId among congenitally infected newborns in northwestern Argentina and support the assumption that human infection by T. cruzi in the Southern Cone countries of Latin America is due principally to T. cruzi II.